Descriptive epidemiology of novel influenza A (H1N1), Andhra Pradesh 2009-2010 - Ramesh R Allam; Manoj V Murhekar; Geetha P Tadi; Prasada R Udaragudi (Wolters Kluwer Medknow Publications, 2013)
Background: The first case of pandemic Influenza A (H1N1) in India was reported from Hyderabad, Andhra Pradesh on 16 th May 2009. Subsequently, all suspected cases seeking treatment from A (H1N1) treatment centers and their contacts were tested. Laboratory confirmed cases were hospitalized and treated with antivirals according to national guidelines. We reviewed the surveillance data to assess the morbidity and mortality due to A (H1N1) in the state of Andhra Pradesh (population-76,210,007) during the period from May 2009 to December 2010. Materials and Methods: We obtained the line-list of suspected (influenza like illness as per World Health Organization case definition) and laboratory confirmed cases of A (H1N1) from the state unit of integrated disease surveillance project. We analyzed the data to describe the distribution of case-patients by time, place and person. Results: During May 2009 to December 2010, a total of 6527 suspected (attack rate: 8.6/100,000) and 1480 (attack rate: 1.9/100,000) laboratory confirmed cases were reported from the State. Nearly 90% of the suspected and 93% of the confirmed cases was from nine districts of Telangana region, which includes Hyderabad. Nearly 65% of total confirmed cases were reported from Hyderabad. The attack rate was maximum (2.6/100,000) in the age group of 25-49 years. The cases peaked during August-October. 109 case-patients died (Case fatality ratio: 7%) and most (80%) of these patients had comorbid conditions such as diabetes (24%), chronic obstructive pulmonary disease (20%), hypertension (11%) and pregnancy (11%). Case fatality was higher (16%) among patients who were older than 60 years of age compared with other age groups. Conclusions: In Andhra Pradesh, H1N1 transmission peaked during August-October months and predominately affected adults. Case fatality was higher in patients older than 60 years with comorbid conditions.